Hydrolysis of cellulose into reducing sugars in ionic liquids. (15th January 2016) - Liu, Xianxiang; Xu, Qiong; Liu, Junyi; Yin, Dulin; Su, Shengpei; Ding, Hui
Abstract: An effective method was developed for the production of reducing sugars (RS) from the hydrolysis of cellulose over a magnetic acid catalyst. The sulfonation of the core–shell structured Fe3 O4 @C with Fe3 O4 as a magnetic core could generate the magnetic acid catalyst (Fe3 O4 @C-SO3 H). The hydrolysis of cellulose was performed under several crucial conditions. Hydrolysis of cellulose in ionic liquid 1-butyl-3-methyl imidazolium chloride ([BMIM]Cl) was greatly affected by the content of water. The highest RS yield and glucose selectivity were obtained in 72.1% and 82.5% at 110 °C after 3 h with the weight ratio of [BMIM]Cl to water being 20. It should be mentioned that this catalyst not only owns the high stability but also can be facile recovered by an external magnet.